+0  
 
+1
149
3
avatar

Triangle AHI is equilateral. We know BC, DE, and FG are all parallel to HI and AB = BD = DF = FH. What is the ratio of the area of the trapezoid FGIH to the area of triangle AHI? Express your answer as a common fraction.

 

Guest Feb 13, 2018
 #1
avatar+541 
+1

I will call the distance from B to C x.

Since all of the points are equal distance from eachother, \(FG = 3x \operatorname{and} HI = 4x\).

Area of a trapezoid = \(^{1}\!\!/\!_{2}(b_1+b_2)\times h\), where h = height, b1 = length of bottom, and b2 = length of top.

Area of FGIH = \(7x(\tfrac{\sqrt{3}}{2}x)=\tfrac{7\sqrt{3}}{2}x^{2}\)

Area of ABC = \(x(\tfrac{\sqrt{3}}{2}x)=\tfrac{\sqrt{3}}{2}x^{2}\)

Area ratio of FGIH to ABC = \(\tfrac{7\sqrt{3}}{2}x^{2}:\tfrac{\sqrt{3}}{2}x^{2}\) --> \(7:1\)

helperid1839321  Feb 13, 2018
 #2
avatar+86859 
+1

Thaks, helperid...here's an alternative solution

 

Without a loss of generailty we can let  AB  = 1

 

So   AHI  =   (1/2)(4)*2 sin (60)  =  4√3       (1)

Area  of  AFG  =  (1/2)(3)^2 sin (60) = (9/4)√3    (2)

 

So area of trapezoid  FGIH  =   √3 [ 4 - 9/4]  = √ 3 [ 7/4]

 

So  ratio of area of trapezoid FGIH  to AHI  =

 

√3 {7 /4]  / [  4√3 ]   =   7 / 16

 

EDIT TO CORRECT AN IDIOTIC ERROR  !!!!

 

 

cool cool cool

CPhill  Feb 13, 2018
edited by CPhill  Feb 13, 2018
 #3
avatar+19480 
+2

Triangle AHI is equilateral. We know BC, DE, and FG are all parallel to HI and AB = BD = DF = FH.
What is the ratio of the area of the trapezoid FGIH to the area of triangle AHI?
Express your answer as a common fraction.

 

 

\(\text{Let $FG = s $} \\ \text{Let $HI = c $} \\ \text{Area of the triangle $AHI = A_{AHI}$ } \\ \text{Area of the triangle $AGF = A_{AGF}$ } \\ \text{Area of the trapezoid $FGIH = A_{FGIH}$ } \\ \text{Let $AK = h$ (height of the triangle$_{AGF}$) } \\ \text{Let $AL = H$ (height of the triangle$_{AHI}$) } \\ \text{Let $AF = \frac34 c $}\)

 

1.

\(\begin{array}{|rcll|} \hline A_{AHI} &=& A_{AGF} + A_{FGIH} \\\\ \dfrac{cH}{2} &=& \dfrac{sh}{2} + \left( \dfrac{s+c}{2}\right)(H-h) \quad & | \quad \times 2 \\\\ cH &=& sh + (s+c)(H-h) \\\\ \not{cH} &=& \not{sh} + sH-\not{sh}+\not{cH}-ch \\\\ \mathbf{ch} &\mathbf{=}& \mathbf{ sH } \qquad (1) \\\\ &\text{or}& \\\\ \mathbf{\dfrac{s}{c}} &\mathbf{=}& \mathbf{\dfrac{h}{H}} \qquad (2) \\ \hline \end{array}\)

 

2.

\(\begin{array}{|rcll|} \hline \text{ratio} &=& \dfrac{ A_{FGIH} } {A_{AHI}} \\\\ &=& \dfrac{ \left( \dfrac{s+c}{2}\right)(H-h) } {\dfrac{cH}{2}} \\\\ &=& \dfrac{(s+c)(H-h)}{cH} \\\\ &=& \dfrac{sH-sh+cH-ch}{cH} \quad & | \quad ch=sH \qquad (1) \\\\ &=& \dfrac{cH-sh}{cH} \\\\ &=& 1-\dfrac{sh}{cH} \quad & | \quad \dfrac{s}{c} = \dfrac{h}{H} \qquad (2) \\\\ &=& 1-\dfrac{h^2}{H^2} \\\\ \mathbf{\text{ratio}} & \mathbf{=} & \mathbf{ 1-\left(\dfrac{h}{H}\right)^2} \\\\ && \boxed{\mathbf{3.}\\ \dfrac{h}{\frac34 c} = \dfrac{H}{c} \\ h = \frac34 c \cdot \dfrac{H}{c} \\ h = \frac34 \cdot H \\ \mathbf{\dfrac{h}{H} = \frac34} } \\\\ \mathbf{\text{ratio}} & \mathbf{=} & \mathbf{ 1-\left(\frac34 \right)^2} \\\\ &=& 1- \frac{9}{16} \\\\ &=& \frac{16-9}{16} \\\\ &\mathbf{=}& \mathbf{\dfrac{7}{16}} \\ \hline \end{array}\)

 

So  the ratio  of areas is \(\mathbf{\dfrac{7}{16}}\)

 

laugh

heureka  Feb 13, 2018
edited by heureka  Feb 13, 2018
edited by heureka  Feb 13, 2018

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.